Factors associated with delays in seeking tuberculosis treatment among patients at Muhima district hospital, Rwanda - Nwankwo, Chinenye Mercy; Omar, Yasmin Umubyeyi (International Journal Of Community Medicine And Public Health, 2020)
Background: Few studies exist in Rwanda to establish the reasons behind delays in seeking treatment in the health institutions which further affected timely diagnosis and case detection. The study investigated factors associated with delays in seeking treatment among tuberculosis (TB) patients at Muhima District Hospital, Rwanda. Methods: The study adopted descriptive cross- sectional study of 49 smear-positive TB patients derived using proportion estimation of case registry (November 2016 to January 2017) newly- diagnosed patients, first and second months treatment. Systematic sampling technique used to select 60 TB patients from target population. Data collected by researcher and trained research assistant, using a close- ended questionnaire through a translation in local dialect. Results: About 49% (24) of the smear- positive TB patients experienced delayed in seeking treatment for more than 180 days (6 months). Also 53% (26) were within the 36-45 age-cohort, while majority 75.5% (37) of the respondents was male. About 57% (28) of the respondents have poor knowledge of TB transmission. Similarly, about 51% (25) were the results on the perception of taking anti- TB medication, while median time interval from onset of symptoms and initiation of treatments was 45 days, average 71 days between 15 -180 days. Conclusions: Statistically significant relationship exist between initial source of treatment using home remedies (p=0.0) and private insurance cover (p=0.0) in relation to delay, which further contributed to delay among majority. Recommendations of the study are strengthening medical services utilization, improving case detection, medical infrastructures and collaboration with non- formal healthcare practices.